Mesenchymal Stem Cell-Derived Exosomes Exhibit Promising Potential for Treating SARS-CoV-2-Infected Patients - Alok Raghav; Zeeshan Ahmad Khan; Viabhav Kumar Upadhayay; Prashant Tripathi; Kirti Amresh Gautam; Brijesh Kumar Mishra; Jamal Ahmad; Goo-Bo Jeong (Cells, 2021)
The novel coronavirus severe acute respiratory syndrome-CoV-2 (SARS-CoV-2) is responsible for COVID-19 infection. The COVID-19 pandemic represents one of the worst global threats in the 21st century since World War II. This pandemic has led to a worldwide economic recession and crisis due to lockdown. Biomedical researchers, pharmaceutical companies, and premier institutes throughout the world are claiming that new clinical trials are in progress. During the severe phase of this disease, mechanical ventilators are used to assist in the management of outcomes; however, their use can lead to the development of pneumonia. In this context, mesenchymal stem cell (MSC)-derived exosomes can serve as an immunomodulation treatment for COVID-19 patients. Exosomes possess anti-inflammatory, pro-angiogenic, and immunomodulatory properties that can be explored in an effort to improve the outcomes of SARS-CoV-2-infected patients. Currently, only one ongoing clinical trial (NCT04276987) is specifically exploring the use of MSC-derived exosomes as a therapy to treat SARS-CoV-2-associated pneumonia. The purpose of this review is to provide insights of using exosomes derived from mesenchymal stem cells in management of the co-morbidities associated with SARS-CoV-2-infected persons in direction of improving their health outcome. There is limited knowledge of using exosomes in SARS-CoV-2; the clinicians and researchers should exploit exosomes as therapeutic regime.